1999
DOI: 10.1002/1531-8257(199905)14:3<436::aid-mds1008>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment withL-dopa/carbidopa orL-selegiline on striatal dopamine transporter SPECT imaging with [123I]?-CIT

Abstract: The effect of subchronic treatment with l‐dopa/carbidopa or l‐selegiline on striatal dopamine transporters (DAT) was examined in patients with idiopathic Parkinson's disease with SPECT (single photon emission computed tomography) using [123I]β‐CIT (2β‐carbomethoxy‐3β‐[4‐iodophenyl]tropane) as the radiotracer. Patients who were not currently being treated with these medications were given either 750 mg l‐dopa/carbidopa per day (n = 8) or 10 mg l‐selegiline per day (n = 8). [123I]β‐CIT imaging was performed thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 22 publications
6
77
1
Order By: Relevance
“…For animal studies, the results might be affected by the methodologies such as dose of L-DOPA, administration route, administration period and DAT expression status. Whereas, in nonhuman primates and human studies, L-DOPA does not affect the DAT binding (17)(18)(19). In conclusion, L-DOPA effect on DAT binding are unpredictable.…”
Section: Therapeutic Drug Effects On [ 18 F]fe-pe2i Bindingmentioning
confidence: 74%
“…For animal studies, the results might be affected by the methodologies such as dose of L-DOPA, administration route, administration period and DAT expression status. Whereas, in nonhuman primates and human studies, L-DOPA does not affect the DAT binding (17)(18)(19). In conclusion, L-DOPA effect on DAT binding are unpredictable.…”
Section: Therapeutic Drug Effects On [ 18 F]fe-pe2i Bindingmentioning
confidence: 74%
“…Dopaminergic treatment can change the amount of available dopamine at the synaptic level, which may differentially influence the regulation of AADC and DAT. Although a number of studies have not revealed an effect of dopaminergic treatment on presynaptic dopaminergic imaging measures, 8,24,25 other evidence suggests that dopaminergic treatment can affect these parameters in PD patients. 26,27 Specifically, Guttman et al 27 reported a decline in DAT binding after treatment with levodopa, which was not significant after pramipexole treatment.…”
Section: Dopaminergic Imaging In Parkinsons Disease: Neuroprotection mentioning
confidence: 99%
“…In addition, DAT imaging may be of value for assessing neuroprotective therapies (Pirker et al, 2002). Various authors have shown that treatment with Ldopa or dopaminergic agonists in PD does not cause significant occupation or modulation in the number of striatal DAT labed with β-CIT (Innis et al, 1999;Ahlskog et al, 1999). However, it should be noted that all studies are limited by the small sample size and short treatment duration.…”
Section: Degenerative Parkinsonismsmentioning
confidence: 99%